Evaluation of bleeding pattern,side effect and satisfaction with subdermal contraceptive etonogesterel implant(implanon): a comparison between postpartum and non postpartum user - Abd. Wahab, Noraziana; A. Rahman, Nor Azlina; Mustafa, Kamarul Bahyah; Awang, Mokhtar; Sidek, Ayu Aszliana (2013)
Objective : The aim of this study was to compare the bleeding pattern, side effects and level of satisfaction between postpartum and non post partum Implanon® users. Study design : A prospective study was conducted from July 2010 till June 2012 at Hospital Tengku Ampuan Afzan, Pahang. A total of 110 women ( 60 postpartum and 50 non postpartum women ) who had Implanon inserted, were followed up at 3 and 6 months after insertion. The bleeding pattern, side effects and satisfaction level were analyzed and compared accordingly. Result : The mean age for postpartum group was 31.2 and for non postpartum group was 33.6.There was no difference in body mass index and parity between these two groups. Majority of the Implanon® users were using Oral Contraceptive Pills as previous method of contraception. There was no difference in bleeding pattern at 3 months between postpartum and non postpartum women. However there was significant difference at 6 months for amenorrhoea and infrequent bleeding pattern (p value of 0.005 and 0.024 respectively). About half of the users from each group had the side effects of weight gain ( 53.3% postpartum vs 56.0% non postpartum ) There was significant difference of side effects of headache and acne between postpartum and non postpartum women. Despite the side effects, majority of the users from both groups satisfied with this method of contraception ( 93.3% of postpartum and 88.0% of non postpartum ). Conclusion : Implanon® is a highly effective long acting reversible hormonal contraception. Weight gain was the most common side effect reported. There was significant difference in bleeding patterns and non menstrual side effects between post partum and non postpartum users of Implanon® in the first six months of usage. The overall satisfaction was high among most users.